1997
DOI: 10.1177/0021955x9703300405
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Polyol Functionality on Water Blown Rigid Foams

Abstract: Rigid foam processing and performance issues have all presented themselves as problems to be overcome as the polyurethane industry replaces chlorofluorocarbon (CFC) blowing agents with alternatives such as hydrochlorofluorocarbons (HCFC), hydrofluorocarbons (HFC), isomers of pentane and water. These problems include dimensional stability, foam flowability, formulation viscosity, friability, substrate adhesion, cycle times, cost, temperature resistance, insulation performance, k-factor aging, blowing agent solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…6 -f u n c t i o n a l f o a m w a s w o r s e t h a n t h a t o f 4.8-functional foam. Similar result also appeared in Tabor's study [7] , but no appropriate explanation was given. This is due to the fact that mixing of the mixture became more difficult and caused blowing efficiency to decrease at the same stirring rate when polyether polyol with higher viscosity such as 5.6-functional polyol was used to prepare rigid foams.…”
Section: Effect Of Functionality On Density and Mechanical Propertiessupporting
confidence: 75%
See 1 more Smart Citation
“…6 -f u n c t i o n a l f o a m w a s w o r s e t h a n t h a t o f 4.8-functional foam. Similar result also appeared in Tabor's study [7] , but no appropriate explanation was given. This is due to the fact that mixing of the mixture became more difficult and caused blowing efficiency to decrease at the same stirring rate when polyether polyol with higher viscosity such as 5.6-functional polyol was used to prepare rigid foams.…”
Section: Effect Of Functionality On Density and Mechanical Propertiessupporting
confidence: 75%
“…Since water is a nonozone depleting, non-toxic and cheap blowing agent, some researches on water blown rigid foams and their applications have been performed [4][5][6] . However, compared to the CFCs blown rigid foams, water blown rigid foams encounter some problems such as dimensional stability, foam flow-ability, formulation viscosity, friability, substrate adhesion, insulation performance, K-factor aging and blowing agent solubility [7,8] . A broad study of different effects of polyol, blowing agent, MDI and catalyst on foam properties is very necessary to address these issues.…”
Section: Introductionmentioning
confidence: 99%
“…Cell size affects the mechanical properties by spreading the compressive/tensile stresses to the more numerous structures available in small cell size foams to avoid concentrating the stresses onto fewer larger cell structures. So, the mechanical properties are expected to improve with the decrease of cell size [7] . In addition, according to heat transfer theory of rigid foams, about 10%-15% of the heat transfer of rigid foam can be directly attributed to the radiation, which can be minimized by reducing the cell size of the foam [14] .…”
Section: Effect Of Water Level On Cell Size and Morphology Of Rigid Fmentioning
confidence: 99%
“…Tabor et al [7] investigated the effect of polyol functionality on water blown rigid foams. In their work, it was shown that polyol functionality played an important role in determining the adhesion to aluminum, cell size, K-factor, dimensional stability and glass transition temperature of foam.…”
mentioning
confidence: 99%
“…For example the heat insulating polystyrene foam is undesirable because of its high flammability. [1] The heat and sound insulating polyurethane foams tend to degrade strongly in the presence of humidity by losing their use-value. [2] The fire insulating asbestos sheet is banned because of its carcinogenic effect.…”
Section: Introductionmentioning
confidence: 99%